Public health governance mechanisms of Thailand in response to COVID-19 - Ungsuchaval, Theerapat; Kumlungpat, Chatchada (Journal of Social Sciences Naresuan University, 2020)
The Covid-19 pandemic can be regarded as a mega health crisis which has challenged the governance capacity of the state. Overall, governmental responses to the crisis were heavily relied on administrative power and orders signifying the character of the bureaucratic state that regulates governance mechanisms at the central. This research investigated governance mechanisms of disease control of the Thai public health system and found that three types of health governance mechanism designed to properly response to the health crises have been employed: decision-making mechanism, communication mechanism, and operational mechanism. These health governance mechanisms can, in effect, be regarded as effective government mechanisms regulated by bureaucracy. This article also speculate about the interesting interaction between the political elites and bureaucrats in the governance of Covid-19.